Study of effect of friction stir welding parameters on impact energy of AA7075-T6 - Hao, Duong Dinh; Tra, Tran Hung; Hoa, Vu Cong (Vietnam Journal of Science and Technology, 2016)
The influences of the tool rotation speed (denoted w) and the welding speed (denoted v) on the impact energy at the representative zones in the friction stir welding (FSW) of AA7075-T6 were investigated. Here, the standard V–Notched specimens were applied in which the notches were addressed at the stirred zone (SZ), the heat affected zones (HAZ) in both the advancing side and the retreating side and the mixed zone (MZ). The experimental results showed that, in all cases, the lowest impact energy is located at the stirred zone and that energy seems to be increased from the SZ to the HAZ across the welding. Furthermore, it is also found that the impact energy is decreased when the ratio of rotation speed to welding speed (w/v) is increased. The microstructure, the temperature distribution, and the hardness in and around the welded zone were considered and discussed.